Estratégias de enfrentamento em crianças em situação pré-cirúrgica: relação com idade, sexo, experiência com cirurgia e estresse - Carnier, Luciana Esgalha [UNESP]; Padovani, Flávia Helena Pereira [UNESP]; Perosa, Gimol Benzaquen [UNESP]; Rodrigues, Olga Maria Piazentin Rolim [UNESP] (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2015)
This study's aim was to verify coping strategies among children aged between 7 and 12 years old who will be experiencing surgery and the potential relationship of coping strategies with sociodemographic variables, stress in children and in companions, and the child's prior experience with surgery. A total of 58 children hospitalized and waiting for elective surgeries responded to the Assessment Instrument of Coping to Hospitalization and an instrument to assess stress. The companion received a sociodemographic questionnaire and the Lipp Stress Symptom Inventory. Problem-solving strategies and distraction were the most frequent strategies used, while social withdrawal and opposition were the least frequent. Girls and children of stressful parents used emotion regulation strategies with significantly more frequency. Likewise, greater cognitive restructuring was observed in older children and those with prior experience with surgeries. The results show the need to consider the studied variables when developing pre-operative preparation programs.

O estudo objetivou verificar as estratégias de enfrentamento de crianças, com idade entre 7 e 12 anos, em situação pré-cirúrgica, e sua relação com variáveis sociodemográficas, presença de estresse na criança, no acompanhante e experiência prévia com cirurgia. Para tanto, 58 crianças internadas para realização de cirurgias eletivas responderam ao instrumento de avaliação das estratégias de enfrentamento da hospitalização e a um questionário de avaliação do estresse. O acompanhante respondeu a um levantamento sociodemográfico e ao inventário de sintomas de estresse de Lipp. As estratégias mais utilizadas foram distração e solução do problema e as menos utilizadas, afastamento social e oposição. Meninas e filhos de pais com estresse usaram significativamente mais estratégias de regulação da emoção. Observou-se maior uso de reestruturação cognitiva em crianças mais velhas e com experiência prévia em cirurgia. Os resultados sinalizam a necessidade de considerar as variáveis estudadas quando da elaboração de programas de preparação cirúrgica.
Coping strategies among children in a pre-surgical situation: Relationship with age, gender, experience with surgery and stress
Keywords: Coping; Child hospitalized; Stress; Coping; Criança hospitalizada; Estresse